Early Detection of Vascular Obstruction in Microvascular Flaps Using a Thermographic Camera - Cruz-Segura, Alejandro; Cruz-Domínguez, María P.; Jara, Luis J.; Miliar-García, Ángel; Hernández-Soler, Alejandro; Grajeda-López, Pedro; Martínez-Bencomo, Michel A.; Montes-Cortés, Daniel H. (Journal of Reconstructive Microsurgery, 2019)
Background In microsurgical reconstruction, vascular obstruction occurs in approximately 20% of patients. Close monitoring is central to their care. Clinical/Doppler detection of vascular obstruction could be enhanced by thermography.Methods A diagnostic test design included consecutive cases of hospitalized patients, ≥18 years old, who underwent surgery with free flaps. Two researchers separately evaluated patients with clinical/Doppler methods and thermographic camera hourly for 24 hours, every 2 hours for the next 24 hours, and then every 3 hours until discharge. The gold standard was visualization of thrombus or vascular obstruction during surgical reintervention. Sensitivity, specificity, positive/negative predictive value (PPV/NPV), and a delta temperature receiver operating characteristic (ROC) curve were calculated.Results A total of 2,364 tests were performed with a thermographic camera in 40 patients (31 females, 9 males) aged 50.12 ± 9.7 years. There were 28 deep inferior epigastric perforator, 5 anterolateral thigh, 3 radial, 2 scapular, 1 fibular, and 1 anteromedial thigh flaps included. Six (15%) had postoperative vascular obstruction (5 venous and 1 arterial). One flap developed partial necrosis and one total necrosis (overall survival 97.5%). ROC curve (area 0.97) showed the best results at ≥ 1.8°C of difference to the surrounding skin. Considering two consecutive positive evaluations, the sensitivity was 93%, specificity 96%, PPV 57%, and NPV 99%. The thermal imaging camera allows to identify the obstruction between 2 and 12 hours before the clinical method.Conclusion Utilizing a thermographic camera can reduce detection time of vascular obstruction by several hours in microvascular free flaps that include the cutaneous island. This method proves useful for early diagnosis of postoperative vascular obstruction.
Keywords: microvascular flaps; thermography; vascular obstruction